MOBILIZATION OF MINI PILE UPLIFT RESISTANCE IN SAND - Andikanoza Pradiptiya; Yuwono Yuwono; Handi Sudardja; Istiatun Istiatun (Politeknik Negeri Jakarta, 2015)
Abstract Shaft resistance of tension pile will be fully mobilized at certain displacement. Some structures impose limits to the displacement of pile with a relatively small value in order not to cause damage. Therefore, it is necessary to know the behavior of pile resistance reaction against load that works in every displacement. The study was conducted using the model of single pile made of concrete with a length of 0,2 m ; 0,3 m ; 0,4 m and each diameter 0,02 m ; 0,03 m ; 0,04 m. The model pile is jacked in sand that has been compacted in a box and then given uplift load that refers to the ASTM D3689-07 procedure E. Pile resistance reaction is shown by pile friction modulus and determined by mobilized unit shaft resistance and pile displacement relationship. The results showed that mobilization of uplift resistance of mini pile that has been counted using friction modulus can only approach the value of true observations, so that it requires further consideration as design parameter. Keywords : Mini pile, sand , uplift resistance.